Contextualising sin for cross-cultural evangelism - Hibbert, Richard Y. (Missiology, 2014)
This article explores the miscommunication of the concept of sin and consequently of the gospel due to mismatches between missionaries’ and host people’s understandings of sin. Examples of the miscommunication of sin in several cultural contexts due to gospel communicators’ limited and fixed understanding of sin are given. The Bible’s portrayals of both the multifaceted nature of sin and the corresponding multifaceted nature of the gospel are examined. Based on these, an approach to more effective communication of the concept of sin is outlined, which includes appreciating its multifaceted nature, analysing how the local people view it, and examining how the Bible speaks to the local people’s particular understanding of sin.